Overview of activities at the ISL hypersonic shock tunnels. (2nd March 2011) - Gnemmi, Patrick; Srulijes, Julio; Seiler, Friedrich
The main activities of the 'Aerothermodynamics and Shock Tube Laboratory' deal with studies of the aerothermodynamics of high-speed projectiles and missiles and their related steering systems, of sub-munitions ejected from tactical ballistic missiles and of interceptors of re-entry vehicles. The main advantage of using shock tunnels for aerothermodynamic investigations is the reproduction of real flight conditions of vehicles at a very low cost. Many studies are conducted with industrial partners to gain a realistic insight into the physics of the flow around models of real vehicles and to build a useful database for the validation of their numerical simulations. The present paper is dedicated to the measurement methods in use at the hypersonic shock tunnels and to the recent research subjects investigated in these facilities.